Emergence of coagulase-negative staphylococci. Issue 4 (2nd April 2020) - Becker, Karsten; Both, Anna; Weißelberg, Samira; Heilmann, Christine; Rohde, Holger
ABSTRACT: Introduction : Compared to Staphylococcus aureus, coagulase-negative staphylococci (CoNS) are characterized by a lower capacity to cause acute, live-threatened infections. CoNS are, however, of ever increasing importance as pathogens causing infections in immunocompromised patients and after foreign-material implantation. Typically, antibiotics fail to cure foreign body-related infections and removal of the implanted device is inevitable. Areas covered : This review focuses on the emergence of CoNS species, their pathogenic potential in particular due to their ability to form therapy-refractory biofilms on biotic and abiotic surfaces and evasion strategies to resist host response and antibiotic treatment. Their medical significance and proven and novel therapy strategies are discussed. Expert opinion : CoNS contribute significantly to morbidity and socio-economic costs. The anticipated developments in modern medicine, in particular the increasing use of foreign materials and the rising numbers of immunocompromised patients, as well as the changing demographic and hospital-related factors will inevitably contribute to further emergence of CoNS infections. Increasing rates of (multi-)resistant CoNS strains will limit the therapeutic armamentarium and aggravate treatment strategies. Increased research is necessary to understand their role as resistance and virulence gene reservoir and to reduce CoNS infections by the development of innovative colonization-preventing materials and other CoNS-tailored treatment strategies.